La littérature francophone mauricienne, un écho à la littérature dix‑huitièmiste comme héritage ? - Dosoruth, Sonia (Romanica Silesiana)
When the French novelist Bernardin de Saint‑Pierre wrote Paul and Virginia, in 1787, little did he know the international impact the book would have. Indeed, this novel emblematises the whole of the Mauritian francophone literature. This is because the vast majority of authors, from the colonial period to date, have internalised some form of mimicry of the book. The legacy it supports ranges from the representation of the utopian island to the ideological and aesthetics values of The Enlightenment, all of which pass through culture, History, the marks of anti‑slavery movement, or the works of Nature. Key words: The Enlightenment, Mauritius, nature, realism, literature